Enhancing monitoring systems with interference-handling radio frequency direction finding: BMKG C-Band weather radar in West Kalimantan Indonesia case study - Kusumawardhani, Eka; Putra, Leonardus Sandy Ade; Mawaldi, Ikbal; Kurniawan, Ade; Kurnawan, Wawan (International Journal of Electrical and Computer Engineering (IJECE), 2025)
This study investigates the effectiveness of the interference-handling radio frequency direction finding (RFDF) monitoring system in detecting and localizing interference sources near the BMKG C-Band weather radar in West Kalimantan, Indonesia. We conducted field tests varying interference transmitter power levels (0-30 dBm) and distances (100, 500, and 1,000 m) from the radar. Results indicate the RFDF system's robust performance, consistently detecting interference within 5-20 minutes and accurately localizing sources with minimal deviation from actual positions. The findings confirm the system's superiority over traditional manual methods, offering a reliable solution for interference management in weather radar operations. However, limitations include controlled test conditions and a need for further exploration of the system's efficacy in diverse environmental settings. This research contributes to improving radar reliability and lays the groundwork for future studies to refine RFDF technology for broader meteorological applications.